Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan terhadap Penghindaran Pajak - Elizabeth, Jesica; Mahroji, Mahroji (Jurnal EMT KITA, 2026)
Companies legitimately attempt to lower their tax bills by exploiting tax loopholes; this is called tax avoidance. The purpose of this study is to examine how the Cash Effective Tax Rate (CETR) is affected by ROA, DER, and LN, in relation to tax avoidance. Agency theory, the basis of this study, states that managers tend to make decisions, including those related to corporate tax management, based on their own self-interest, rather than the interests of the owners. Using data from 112 observations from energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2024, this study adopted a quantitative method with multiple linear regression. There is a negative correlation between tax avoidance and profitability, according to the study results. As profits increase, businesses are less likely to engage in tax avoidance strategies. This is in line with agency theory, which highlights the importance of reputation and owner influence on management. At the same time, there is no clear relationship between leverage and company size; this suggests that tax avoidance techniques by energy industry businesses are not always determined by their overall assets or debt levels.